UPAYA MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS X PADA MATA PELAJAEAN SEJARAH MELALUI PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TORNAMENT (TGT) DI SMA NEGERI 14 SEMARANG TA 2022/2023 - Ayna Ayu Alkhairunisa (Historia Pedagogia, 2024)
The history learning at SMA Negeri 14 Semarang for grade X has already implemented the "merdeka" curriculum, which encourages students to be active in seeking information. However, based on observations of history learning in class X3, many students remain passive, which affects their learning outcomes in that class. Therefore, it is crucial to enhance student participation in history learning to improve their learning outcomes. Consequently, teachers need to choose varied and appropriate teaching methods for the classroom. One suitable method is using the word wall media in the form of box questions in teams with the Teams Games Tournament learning model. By using box questions in the Teams Games Tournament learning model, students can be more motivated to learn, achieving learning objectives and improving student learning outcomes. This research is a Classroom Action Research (CAR). The subjects of the research were 35 students of class X3 at SMA Negeri 14 Semarang. The data collection instruments included student worksheets and observation sheets. The sub-topic used was the Acculturation of Islamic Culture and Islamic Kingdoms in Maluku. The research indicators were an improvement in student learning outcomes, with an increase in student learning outcomes from cycle I to cycle II. The research results showed that the average student score in cycle I was 65.7%, which had met the minimum mastery criteria (KKM), and in the second cycle, it increased to 85.7% of students who had met the KKM. From these results, there was an improvement in student learning outcomes by using the word wall box question media.